Edukasi Gerak dan Lagu Tradisional sebagai Media Promosi Sport Tourism Ramah Anak di Kawasan Wisata Alam - Destiana, Evie; Fretisari, Imma; Hapidzin, Rivaldi Indra; Lindiana, Deti (Jurnal Pengabdian Keolahragaan dan Sains, 2025)
The objective of this program is to raise cultural awareness, foster children’s involvement in the preservation of traditional arts, and encourage active community participation in the development of child-friendly sport tourism. The program integrates educational approaches, performing arts, and nature-based tourism activities to create an interactive and enjoyable learning experience for children aged 6 to 12 years. The implementation methods include community needs analysis, the design of training materials for traditional movement and songs, the execution of participatory workshops in open spaces (such as child-friendly integrated public spaces and nature tourism areas), the use of digital technology (regional music applications), and evaluations based on feedback from participants and the community. The program is carried out through collaboration among lecturers, students, local government, and the community. The outcomes of the activities show increased enthusiasm, active participation, and stronger social interaction among children and the local community. The novelty of the program lies in the integration of traditional movement and songs with digital technology as an educational medium for culturally-based child tourism promotion. This community service contributes to strengthening children’s character through cultural arts, developing community-based educational tourism destinations, and preserving local culture through a participatory intergenerational approach. The program serves as a model for inclusive and sustainable cultural tourism development that can be replicated in other tourism areas across Indonesia.